Organizational creativity a practical guide for innovators & entrepreneurs - Puccio, Gerard J.; Cabra, John F.; Schwagler, Nathan (SAGE, 2018)
Organizational Creativity: A Practical Guide for Innovators and Entrepreneurs by Gerard J. Puccio, John F. Cabra, and Nathan Schwagler, is a compelling new text designed to transform the reader into a creative thinker and leader. Arguing that creativity is an essential skill that must be developed, the authors take a highly practical approach, providing strategies, tools, and cases to help readers hone their creative abilities. Whether students are preparing to become entrepreneurs or to work in an established firm, this text will help them survive and thrive in an era of innovation and change.--Provided by publisher.